The Effect of Family Economy on Availability of Family Toilet in Luwohu Village, Bone Bolango District - Bun Yamin M. Badjuka (Humanistic Network for Science and Technology (HNST), 2019)
Toilet facilities that do not meet health requirements can cause infectious diseases to the society. Toilet is residential facility. An average economy condition causes the family unable to build facilities / own defecation place because family income prioritizes more on daily family needs like meal cost and education cost. Therefore eventhough that family has awareness and desire but can not afford to build feces disposal facilities because of fund difficulty. The purpose of this research is to know the effect of family economy to the availability of family toilet at Luwohu Village of Bone Bolango Disctrict. The type of this research was analytic observational research with cross sectional research design. Chi square test result showed X2 countation (7.25) was bigger than X2 table (3.841), with p value = 0.007 which means that there was a very significant effect between family economy to the availability of family toilets at Luwohu Village, with other words the higher family economy was, family toilets were more increasingly available. It is advised that the Government of Luwohu Village, should be able to give motivation to the society to have family toilets or add public facilities like public toilets at least two in every environment and Public Health Centers through sanitation officer should give counseling and techincal assistance at building family toilet and the head of family should work hard to have family toilet at least in a simple form but meets the health requirements. Keywords: Family economy, Toilet, Availabilty of toilet